Primary and Posttraumatic Knee Osteoarthritis in the Military - Rodriguez, Marina J.; Garcia, E'Stephan J.; Dickens, Jon F. (The Journal of Knee Surgery, 2019)
Osteoarthritis is a particularly burdensome and career-limiting condition for military service members. The daily demands of military service place the service members at a baseline increased risk of developing primary OA as well as increased risk of acute knee injuries that further predispose to developing posttraumatic OA. There are multiple treatment options available for primary and posttraumatic OA from osteotomy to arthroplasty.
Keywords: posttraumatic osteoarthritis; military; OA